Personality traits of respondents with different attitudes towards the COVID-19 epidemic - Z. H. Каjtukova (Вестник университета, 2021)
An empirical study of the psychological characteristics associated with attitudes towards the spread of the COVID-19 virus is presented. The attitude towards the spread of the COVID-19 virus is defined as a system of partial subjective assessments of the essential characteristics of a given situation: the potential danger of infection with the virus, information coverage of events in the media, health-preserving measures of official institutions. A classification of types of attitudes towards the spread of the COVID-19 virus is proposed based on combinations of various partial subjective assessments of the essential characteristics of the situation of the spread of the virus. The article reflects the results of an empirical study of the personality traits of respondents with different attitudes towards the spread of viral infection: significant positive and negative correlations between the types of attitudes towards the pandemic and respondents’ copping strategies, types of relationships and such personal characteristics as extraversion – introversion, attachment – alienation.